Autobiography: An Autopsy. Issue 1 (1st March 2021) - Menu, Jean-Christophe; Neaud, Fabrice
Abstract: In this email exchange, Jean-Christophe Menu inveighs against the deterioration of comics autobiography into a formulaic 'genre'. Fabrice Neaud maintains that the autobiographical enterprise is necessarily a dangerous undertaking in which a precarious subject comes into being, unlike the 'proximate' autobiography featuring a ready-made persona in search of peer approval. He employs a Darwinist evolutionary metaphor to demonstrate the colonisation of the ecological niche that houses comics autobiography by an 'autobiography-lite' better adapted to the market. He details the criticisms that have been made of his work ('egotistical', or formally over-conservative) and laments the tendency to equate artless scribbles with 'sincerity'. Menu regrets that a distanced and selective portrayal of family life can be read as invasive of privacy, with devastating legal consequences.